BIOLOGIA REPRODUTIVA DE COTESIA FLAVIPES (CAM.). III. INTERFERÊNCIA MÚTUA: FÊMEAS FECUNDADAS POR UM E DOIS MACHOS - Campos-farinha, A.e. De C.; Chaud, J. [UNESP] (Instituto Biológico, 2025)
Cotesiaflavipes females mated to one and two males were allowed to parasitize one Diatraea saccharalis larva No interference or competition between them were observed suggesting that this species avoids superparasitizing.

Foi observado o comportamento de fêmeas de Cotesia flavipes inseminadas por um e dois machos que foram colocadas na presença de uma lagarta de 5º ínstar de Diatraea saccharalis. Não houve nenhuma interferência ou competição entre as fêmeas sugerindo que esta espécie evita superparasitar.
REPRODUCTIVE BIOLOGY OF COTESIA FLAVIPES (CAM.). III. MUTUAL INTERFERENCE: FEMALES MATED TO ONE AND TWO MALES
Keywords: Diatraea saccharalis; Cotesiaflavipes; superparasitism; mutual interference; Diatraea saccharalis; Cotesiaflavipes; superparasitismo; interferência mútua